2007
DOI: 10.1002/jez.b.21157
|View full text |Cite
|
Sign up to set email alerts
|

Development and evolution of chordate cartilage

Abstract: Deuterostomes are a monophyletic group of an imals con tai ni n g vertebrates, lancelets, tunicates, hemichordates, ech inoderms, and xenoturbellids. F our out of these six extant groups-vertebrates, la ncelets, tunicates, and h emichordates-have pharyngeal gill slits. All groups of deuterostome an im als that have pharyngeal gill slit s also have a pharyn geal sk eleton supporting the pharyngeal ope nin gs, except tunicates. We previously found that pharyngeal cartilage in hemichordates and ceph aloch ordat e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 63 publications
6
71
0
Order By: Relevance
“…Studies in chordates suggest that secretion of a fibrillar collagen with properties similar to the vertebrate type II collagen by endodermal epithelium was the ancestral mode of making pharyngeal cartilages, the gill bars supporting pharyngeal gill slits. The morphological similarity of these cartilage-like structures to hypertrophied basal laminae has also been discussed in several reports (Benito and Pardos, 1997;Rychel et al, 2006;Rychel and Swalla, 2007).…”
Section: Col2-cre Is Expressed In Embryonic Kidney Epitheliummentioning
confidence: 79%
“…Studies in chordates suggest that secretion of a fibrillar collagen with properties similar to the vertebrate type II collagen by endodermal epithelium was the ancestral mode of making pharyngeal cartilages, the gill bars supporting pharyngeal gill slits. The morphological similarity of these cartilage-like structures to hypertrophied basal laminae has also been discussed in several reports (Benito and Pardos, 1997;Rychel et al, 2006;Rychel and Swalla, 2007).…”
Section: Col2-cre Is Expressed In Embryonic Kidney Epitheliummentioning
confidence: 79%
“…Hypotheses discussed in this article are based on the understanding that hemichordates are the sister group to echinoderms, but echinoderms have highly derived adult body plans that share few homologies with chordates (Swalla, 2006). We have shown that hemichordates and lancelets share homologies that are not present in echinoderms or tunicates, such as unusual acellular pharyngeal cartilages (Rychel and Swalla, 2007). Consequently, morphological characters shared between hemichordates and chordates are likely to have been present in the deuterostome ancestor (Swalla and Smith, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Most of these are now rather weakly supported by both morphological and molecular datasets (Peterson et al 1999;Nieuwenhuys 2002;Lowe et al 2003Lowe et al , 2006Ruppert 2005). However, only gill slits, as primary ciliated pouches, may represent an ancestral feature of the deuterostomes (Ogasawara et al 1999;Okai et al 2000;Tagawa et al 2001;Cameron 2002;Rychel et al 2006;Rychel & Swalla 2007) and possibly the post-anal tail (Lowe et al 2003). A much more in depth discussion of hemichordate and chordate potential morphological homologies is discussed in Ruppert (2005).…”
Section: Problems Reconstructing Ancestral Deuterostome Charactersmentioning
confidence: 99%